Health Problems of School-aged Children that Access to Online Media: The Perspective of Working-age Parents in Thailand 4.0 Era - Wonginchan, Atchariya; Tangpukdee, Juraporn; Wonginchan, Suphasak; Kearttiwongkru, Sureeporn; Khonggungong, Sujitra (Nursing Journal CMU, 2021)
Health problems of school-aged children (SAC) who access online media in the Thailand 4.0 era are likely to increase as all sectors focus on driving more innovative activities. As a result, working-age parents (WAPs) focus more on work and less time to care for their children during school age. The objective of this qualitative research was to study the health problems of SAC with access to online media and the perspectives of WAPs. Collection data through in-depth interviews with 36 target groups, and a focus group with representatives via an online program with recordings for easy data curation. Analyze data by the transcribed interviews to synthesize three issues as follows. The parental context of care is important and challenging, how to access online media of SAC, and the health problems are different in each dimension. The study found that the context of WAPs played an important role in making SAC more accessible to online media. Next, smartphone ownership and unrestricted Internet use by SAC will increase the convenience and flexibility of accessing online media for a long time. Lastly, parents’ point of view is to focus more on care and prevention because if it affects the health problems of SAC on one dimension, it will affect other health problems. However, if access to online media tends to rise cannot be avoided, changes in online media access behavior can affect health care. The benefit, if proper access is encouraged, would be a better choice than control. Those involved in the care and prevention of health problems should refer to the context of their parents, the benefits of accessing online media, and its impact on all aspects of health problems, of which these are important.